Siehe Rückseite! Writings on the back in German amateur photographs (1939-1945) - de Luelmo Jareño, Jose María (Eikón / Imago, 2025)
The digital condition has modified not only the status of photographic creation but also that of those photographs prior to its arrival that, for preservation or archiving purposes, have been subjected to digitization. Among other consequences, the conversion of these photographs into mere images has entailed the obliteration of certain material features, such as the marks and inscriptions on the back, of particular importance for their proper characterization. Taking as a paradigmatic case the amateur production of the German contingent in World War II, the research proposes how the study of these physical signs allows not only to contextualize and date the photographs but also to obtain information about their original intention, their value of use or the circumstances of their circulation, all of them of great relevance in this particular case. To test the relevance of this type of material analysis, the article directly analyzes an archive of original and unpublished photographs to date, and focuses on certain particularly significant typologies.